Designing multi-target drugs - Morphy, Richard; Harris, C. John (RSC drug discovery series ;, 2012)
"Multi-target drug discovery (MTDD) is an emerging area of increasing interest to the drug discovery community. Drugs that modulate several targets have the potential for an improved balance of efficacy and safety compared to single targets agents. Although there are a number of marketed drugs that are thought to derive their therapeutic benefit by virtue of interacting with multiple targets, the majority of these were discovered accidentally. Written by world renowned experts, this is the first book to gather together knowledge and experiences of the rational discovery of multi-target drugs. It describes the current state of the art, the achievements and the challenges of the field and importantly the lessons learned by researchers to date and their application to future MTDD."--